2024
DOI: 10.1590/1519-6984.259721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the brown alga, Sargassum muticum extract as an antimicrobial and feeding additives

Abstract: Plant disease administration is difficult due to the nature of phytopathogens. Biological control is a safe method to avoid the problems related to fungal diseases affecting crop productivity and some human pathogenic bacteria. For that, the antimicrobial activity of the seaweed Sargassum muticum methanol and water extracts were investigated against human bacterial pathogens and fungal plant pathogens. By using 70 percent methanol, the seaweed powder was extracted, feeding additives assay, ultrastructure (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…Extract could be used as a promising natural antibacterial agent against E. coli and Salmonella sp. This finding was corroborated by the study of Nofal et al [32] which also found that Nano F3 * 5.90 ± 0.44 d 8.67 ± 0.51 e ab uncommon superscripts indicated significant different (P < 0.05) * Nanoparticles were synthesized with the chitosan: Sargassum sp. Extract:tripolyphosphate ratios of 4:0:2 (Nano F0), 4:1:2 (Nano F1), 4:2:2 (Nano F2), and 4:4:2 (Nano F3).…”
Section: Resultssupporting
confidence: 75%
“…Extract could be used as a promising natural antibacterial agent against E. coli and Salmonella sp. This finding was corroborated by the study of Nofal et al [32] which also found that Nano F3 * 5.90 ± 0.44 d 8.67 ± 0.51 e ab uncommon superscripts indicated significant different (P < 0.05) * Nanoparticles were synthesized with the chitosan: Sargassum sp. Extract:tripolyphosphate ratios of 4:0:2 (Nano F0), 4:1:2 (Nano F1), 4:2:2 (Nano F2), and 4:4:2 (Nano F3).…”
Section: Resultssupporting
confidence: 75%
“…In addition, various phenolic groups have been found in seaweed extracts, with antibacterial activity demonstrated through in vitro methodologies from a wide range of seaweed, including Anthophycus longifolius and Gracilaria gracilis (highlighting the abundancy of flavonoids), with activity against Bacillus subtilis [ 160 , 161 ]; Caulerpa peltata , Caulerpa scalpelliformis , Sargassum aquifolium , Colpomenia peregrina , Ellisolandia elongata , Punctaria latifolia , Punctaria plantaginea , Scytosiphon lomentaria , and Zanardimia typus with inhibition capacity against Staphylococcus aureus [ 139 , 162 , 163 , 164 ]; Sarconema filiforme against Pseudomonas sp. [ 165 ]; Sargassum muticum against B. subtilis , Escherichia coli and S. aureus [ 166 ]; Sargassum tenerrimum against B. subtilis , E. coli, P. aeruginosa , and S. aureus [ 167 , 168 , 169 ]; Sargassum cristaefolium against E. coli and S. aureus [ 164 ]; Gracilaria corticata , S. wightii , and Ulva lactuca against P. aeruginosa and S. aureus [ 170 , 171 ]. In cases of resistant bacteria, some macroalgae extracts have shown higher effectiveness when combined with artificial chemical products, such as antibiotics, demonstrating a positive synergistic activity between the antibiotics and the natural compounds present in the extracts.…”
Section: Phytopathogenic Antibacterial Potential Of Seaweedsmentioning
confidence: 99%
“…In general, flavonoids protect plants against different biotic agents and abiotic stresses and among the many benefits to plants, they are considered signaling molecules in the defense against phytopathogens (Cesco et al, 2012). The fungicidal potential attributed to flavonoids, in terms of inhibiting fungal growth (fungicide effect) or limiting its development (fungistatic effect), or acting as elicitors, is often associated with the diversity and quantity of this class of polyphenols (Stanković et al, 2012;Hassan et al, 2021;Nofal et al, 2024).…”
Section: Discussionmentioning
confidence: 99%